Basal metabolic rate as a protective factor against osteoporosis: a multi-cohort longitudinal study from three international aging databases - Cai, Yuzhou; Dai, Fangyi; Li, Hongyu; Zeng, Yujian; Guo, Peiyu; Zhang, Tong (Frontiers in Nutrition, 2026)
BackgroundOsteoporosis is a major public health burden in aging populations; whether basal metabolic rate (BMR) is independently associated with incident osteoporosis independent of sarcopenia remains unclear.ObjectivesTo examine the association between BMR and incident osteoporosis and whether this relationship is modified by sarcopenia status and demographic factors.MethodsWe analyzed 17,836 adults aged ≥45 years from three longitudinal cohorts—ELSA (n = 3,293), HRS (n = 4,498), and SHARE (n = 10,045). BMR was estimated using the Mifflin–St Jeor equation and modeled as quartiles and per 1-SD. Cox proportional hazards models with progressive adjustment were used; restricted cubic splines assessed dose–response. Subgroup/interaction analyses evaluated effect modification. Sensitivity analyses included exclusion of early events, trimming extreme BMR values, complete-case analyses, and cohort- and sex-specific analyses.ResultsOver a median 11.5 years, 1,490 (8.35%) participants developed osteoporosis. Compared with the lowest BMR quartile, the highest quartile had a 37% was associated with lower osteoporosis risk (HR 0.629, 95% CI 0.494–0.800; p < 0.001). Each +1 SD increase in BMR was associated with an 18% lower risk (HR 0.823, 95% CI 0.758–0.893; p < 0.001). The association was approximately linear and consistent across cohorts but varied by education (P-interaction = 0.007) and smoking (P-interaction = 0.011). Findings were robust across all sensitivity analyses.ConclusionHigher BMR is independently associated with lower incident osteoporosis risk in a linear fashion—beyond sarcopenia and conventional risk factors—with effect modification by education and smoking. As an observational study, causality cannot be established. As an accessible marker of metabolic capacity, BMR may complement existing tools for risk stratification in aging populations.